ASSESSMENT OF USERS PERCEPTION OF ENVIRONMENTAL PERFORMANCE OF UNIVERSITY LIBRARY BUILDINGS IN NIGERIA - Collins A. Anyanwu; Oluwafemi K. Akande (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The Indoor environmental quality of any building can directly affect the wellbeing of the users of the building. The university libraries being a public space designed for learning purposes, must meet important specific indoor criteria such as lighting, acoustics and etc in order to enhance students' academic performance. The aim of this is to examine elements in the indoor environmental condition of university libraries that could enhance user’s educational learning. The objective is to identify and address the potential issues and the challenges encountered by the library use’s that could discourage them from using the library. A survey methodology and the use of questionnaire was adopted to collect data from library users in three (3) universities in the study location (n=484). The response rate recorded 84% having overall reliability test of 0.87. Findings indicate that the respondents agreed that the indoor environmental condition were satisfactory. However further findings suggests that as the environmental condition improves, the users were more inclined to the use of the library. The study concludes that there is need to improve the indoor environmental condition of the library. This would encourage more attention of the library users to harness the library for their educational learning and consequently boost their academic performance.